The Influence Of Teacher Teaching Styles and Leaning Motivation on The Learning Achievement - Mudzakkir, Mudzakkir; Darmawan, Didit (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2024)
Abstract - This study aims to assess the impact of teacher teaching style and learning motivation on the learning achievement of students at SDN Kutisari I/268 Surabaya. With a population of 590 students, a sample of 97 sixth-grade students was selected for this quantitative research. The study employs multiple linear regression to analyze how the independent variables (teacher teaching style and learning motivation) affect the dependent variable (learning achievement). The findings reveal a noteworthy influence of both teacher teaching style and learning motivation on student learning achievement at SDN Kutisari I/268 Surabaya. Teacher teaching styles exhibit a robust positive effect on academic performance, indicating the pivotal role of educators' approaches and strategies in facilitating student comprehension of learning materials. Teachers who employ innovative methods and actively motivate students contribute to a conducive learning environment, leading to improved learning outcomes. Moreover, student learning motivation significantly influences academic achievement, underscoring the importance of intrinsic and extrinsic motivation in encouraging students to engage actively in the learning process and attain high academic success.